Solid electrolyte, powder for producing solid electrolyte, and method for producing solid electrolyte

By coating the surface of NASICON type LTP and LATP solid electrolyte particles with extremely small amounts of cobalt ions to form a thin coating, the problem of producing high-density and high conductivity solid electrolytes at temperatures of 800°C or lower is solved, and an efficient and low-cost production process is achieved.

JP7669033B2Active Publication Date: 2025-04-28NAT INST FOR MATERIALS SCI

Patent Information

Application Number
JP2021119796
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-20
Publication Date
2025-04-28
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently produce NASICON type LTP and LATP solid electrolytes at temperatures of 800°C or lower, resulting in poor phase density and conductivity of the solid electrolytes.

Method used

By uniformly coating the surface of solid electrolyte particles with a very small amount of cobalt ions, a coating with a thickness of lower cobalt content at the atomic layer is formed, and the sintering temperature is reduced to 800°C or less using cobalt as a sintering aid.

Benefits of technology

The high density and excellent conductivity of NASICON type LTP and LATP solid electrolytes are achieved, while avoiding the degradation of electrical properties during high-temperature sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669033000001
    Figure 0007669033000001
  • Figure 0007669033000002
    Figure 0007669033000002
  • Figure 0007669033000003
    Figure 0007669033000003
Patent Text Reader

Abstract

To provide easily sinterable powder which is preferable for production of a NASICON type LTP solid electrolyte, and the NASICON type LTP solid electrolyte having great density and being excellent in electric conductance.SOLUTION: There is provided a solid electrolyte being formed of a sinter body whose bulk part is formed of a NASICON type LTP, and whose neck part has cobalt oxide which exists thereon.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte, a powder for producing a solid electrolyte, and a method for producing a solid electrolyte. [Background technology]

[0002] All-solid-state secondary batteries are highly anticipated as the next generation of rechargeable batteries. The main components of an all-solid-state secondary battery are positive and negative electrodes and a solid electrolyte. In particular, the lithium-ion all-solid-state secondary battery, which is currently attracting attention, uses NASICON-type LTP-based solid electrolytes, which have excellent properties such as electrical conductivity, mechanical strength, and chemical stability, and Li 1.3 Al 0.3 Ti 1.7 LATP solid electrolytes such as (PO4)3 are mainly considered.

[0003] In order to efficiently produce all-solid-state secondary batteries with high productivity and low cost, it is preferable to fabricate the electrodes and the LTP or LATP solid electrolyte by a co-sintering method. LTP and LATP solid electrolytes are generally produced by sintering, and the sintering temperature is 1000°C or higher. On the other hand, the general sintering temperature for olivine-type positive electrode active materials is about 800°C to suppress diffusion with the electrode. For this reason, when sintering together, the sintering temperature is limited to 800°C, lower than that of LTP or LATP solid electrolytes, because the sintering temperature of the positive electrode active material becomes a bottleneck. Incidentally, if sintering is performed at 1000°C, diffusion occurs between the electrode and the LTP or LATP solid electrolyte, causing problems such as poor electrical properties due to the generation of a high resistance phase caused by a solid-state reaction.

[0004] When the sintering temperature is about 800°C, the relative density of LTP and LATP without added sintering aids is about 60%, which is very low compared to about 80% when sintered at 1000°C, and the electrical conductivity is also low.

[0005] Therefore, there has been a demand for an easily sinterable LTP solid electrolyte that can be sintered at a sintering temperature of 800°C or less, can be made dense, and has excellent mechanical strength and electrical conductivity, as well as a powder for producing the solid electrolyte, which is essential for producing the solid electrolyte, and a method for producing the powder and the powder.

[0006] Patent Document 1 discloses an all-solid-state secondary battery and a manufacturing method thereof, which suppresses the diffusion of Li metal elements (Mn, Co, Ni) from a positive electrode active material to a solid electrolyte when an olivine type positive electrode active material and a NASICON type solid electrolyte are co-fired, thereby suppressing the influence during charging and discharging. In this case, a transition metal that diffuses into the electrolyte layer is added, which suppresses the reaction and improves sinterability. Here, the transition metal is added by an oxide, carbonate, or acetate during the synthesis of the electrolyte or to the synthesized electrolyte. Note that the method of adding by an oxide tends to form a structure in which a large amount of sintering aid is left behind or an impurity phase, because nonuniformity occurs in the local structure due to the particle size and particle dispersibility, and there is a problem in controlling the dispersion of the powder particles. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-11864 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the conventional problems described in the Background Art above, and has an object to provide an easily sinterable NASICON-type LTP or LATP solid electrolyte having high density and excellent electrical conductivity, and a powder for sintering suitable for producing the solid electrolyte. Another object of the present invention is to provide a method for producing NASICON-type LTP or LATP solid electrolytes which have a high density and excellent electrical conductivity and are easily sintered at a sintering temperature of 800° C. or less. [Means for solving the problem]

[0009] The configuration of the present invention is shown below. (Configuration 1) The bulk part is made of NASICON type LTP. A solid electrolyte consisting of a sintered body with cobalt oxide present in the neck portion. (Configuration 2) 2. The solid electrolyte according to claim 1, wherein the bulk portion is made of one or more electrolytes selected from the group consisting of NASICON-type LATP and NASICON-type LAGP. (Configuration 3) 2. The solid electrolyte according to claim 1, wherein the bulk portion is made of NASICON-type LATP. (Configuration 4) A powder comprising a solid electrolyte base material and a coating material covering a surface of the solid electrolyte base material, The solid electrolyte base material is made of NASICON type LTP, The coating material contains cobalt (Co) ions; The powder for producing a solid electrolyte, wherein the coating material has a thickness on the order of an atomic layer. (Configuration 5) 5. The powder according to claim 4, wherein the solid electrolyte base material is one or more selected from the group consisting of NASICON type LATP and NASICON type LAGP. (Configuration 6) 6. The powder according to claim 5, wherein the solid electrolyte base material is made of NASICON type LATP. (Configuration 7) 7. The powder of any one of claims 4 to 6, wherein cobalt ions are contained only in the coating material. (Configuration 8) 8. The powder of any one of claims 4 to 7, wherein the coating material comprises cobalt nitrate. (Configuration 9) dissolving a cobalt salt in a solvent capable of forming an azeotrope with water to form a solution; A solid electrolyte base material made of NASICON type LTP is put into the solution and dispersed to prepare a dispersion (slurry); drying the dispersion to obtain a solid; pulverizing the solid material to obtain a powder containing cobalt ions; Molding the powder to obtain a molded body; The molded body is sintered in an environment in which oxygen is present. (Configuration 10) 10. The method for producing a solid electrolyte according to claim 9, wherein the solid electrolyte base material is one or more selected from the group consisting of NASICON type LATP and NASICON type LAGP. (Configuration 11) 10. The method for producing a solid electrolyte according to claim 9, wherein the solid electrolyte base material is a NASICON type LATP. (Configuration 12) 12. The method for producing a solid electrolyte according to any one of claims 9 to 11, wherein the cobalt salt is cobalt nitrate. (Configuration 13) 13. The method for producing a solid electrolyte according to claim 12, wherein the cobalt nitrate is Co(NO3)2·6H2O. (Configuration 14) 14. The method for producing a solid electrolyte according to any one of claims 9 to 13, wherein the solvent includes at least one selected from the group consisting of methanol, ethanol, and propanol. (Configuration 15) 15. The method for producing a solid electrolyte according to claim 14, wherein the solvent is ethanol. (Configuration 16) 16. The method for producing a solid electrolyte according to any one of claims 9 to 15, wherein the sintering is performed in an air environment. (Configuration 17) 17. The method for producing a solid electrolyte according to any one of claims 9 to 16, wherein the sintering temperature is 600°C or higher and 800°C or lower. (Configuration 18) 18. The method for producing a solid electrolyte according to any one of claims 9 to 17, wherein a ratio B / A of a molar amount B of the cobalt salt to a molar amount A of the solid electrolyte base material is 0.001 or more and 0.1 or less. Effect of the Invention

[0010] According to the present invention, there are provided a NASICON-type LTP solid electrolyte having high density and excellent electrical conductivity, a powder for sintering suitable for producing the solid electrolyte, and a method for producing a NASICON-type LTP solid electrolyte having high density and excellent electrical conductivity at a sintering temperature of 800° C. or less. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is an explanatory diagram showing the structure of a sintered body of the present invention. [Diagram 2] FIG. 2 is a flowchart showing the production of the easily sintered solid electrolyte of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram showing the structure of a powder. [Figure 4] FIG. 2 is a characteristic diagram showing the sintering temperature dependence of the relative density of the easily sintered solid electrolyte of the present invention, using the amount of Co added as a parameter. [Diagram 5] FIG. 2 is a characteristic diagram showing the Co-addition dependency of the relative density of the easily sintered solid electrolyte of the present invention, the sintering condition being 800° C. under atmospheric pressure. [Figure 6] FIG. 13 is a characteristic diagram showing the Co additive amount dependence of the relative density of a solid electrolyte when the sintering condition is set to 800° C. under Ar gas. [Figure 7] This is an SEM photograph of the fracture surface structure of a sintered body formed at 800°C without adding Co. [Figure 8] This is an SEM photograph of the fracture surface structure of a sintered body (easy-sintering solid electrolyte (Co-LATP)) formed by adding Co and sintering at 800°C. [Figure 9] This is an SEM photograph of the fracture surface structure of a sintered body (easy-sintering solid electrolyte (Co-LATP)) formed by adding Co and sintering at 1000°C. [Figure 10] FIG. 2 is a characteristic diagram showing the electrical conductivity characteristics of the easily sintered solid electrolyte of the present invention formed by sintering at 800° C. [Figure 11] FIG. 2 is a characteristic diagram showing the electrical conductivity characteristics of the easily sintered solid electrolyte of the present invention formed by sintering at 1000° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The detailed description of the present invention described below may be based on representative aspects, embodiments, and examples, but these are merely examples, and the present invention is not limited to such aspects, embodiments, and examples. In addition, "A~B" indicates A or greater and B or less.

[0013] (Embodiment 1) In the first embodiment, a method for producing a NASICON-type LTP sinterable lithium ion solid electrolyte of the present invention will be described.

[0014] The present invention improves the sinterability of a solid electrolyte by uniformly and simply coating the surface of electrolyte particles with a very small amount of ions of an element (cobalt (Co)) that acts as a sintering aid through a dissolution and precipitation reaction. As a result, a high electrical conductivity and a high relative density necessary and sufficient for a solid electrolyte can be obtained by sintering at a relatively low temperature of, for example, 800°C, at which reaction and diffusion between the electrodes arranged in contact with the solid electrolyte and the active materials that compose the electrodes are suppressed. Here, a high relative density generally results in high mechanical strength. The details are given below.

[0015] FIG. 2 shows a manufacturing process of the all-solid-state electrolyte according to the first embodiment. First, a cobalt salt is dissolved in a solvent (Step S01). In the present invention, the powder for solid electrolyte is characterized in that its surface is covered with a coating material containing cobalt, and a cobalt salt is used as the feed for the coating material containing cobalt. Here, the preferred cobalt salt is cobalt nitrate, and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) is particularly preferred. When cobalt nitrate is sintered, the nitrate group volatilizes and only cobalt remains, making it possible to minimize the amount of remaining impurities. Furthermore, by making it a cobalt nitrate hydrate, especially Co(NO3)2·6H2O, it dissolves well in the solvent, making it possible to obtain a coating material that contains a small amount of cobalt very uniformly.

[0016] The solvent is a solvent capable of forming an azeotrope with water, and is, for example, a solvent containing one or more selected from the group consisting of methanol, ethanol, and propanol, and is particularly preferably ethanol. Here, for example, an example of a solvent containing ethanol is a solvent in which water is added to ethanol. The dissolution is preferably carried out with stirring using a stirrer or application of ultrasonic waves. Room temperature is preferred because it is easy to handle and low cost.

[0017] Next, the NASICON type LTP solid electrolyte base material is put into the solvent and dispersed to prepare a dispersion (step S02). Here, it is more preferable that LTP is one or more selected from the group consisting of LATP and NASICON type LAGP. By using LATP and / or LAGP, it becomes easier to obtain a solid electrolyte with higher performance. Here, the LATP in the present invention is a compound having a ratio of the number of Al atoms constituting the LATP, x(Li 1+x Al x Ti 2-x Lithium-aluminum-titanium-phosphate compounds in which x in (PO4)3 is 0 or more and 1 or less. 1.3 Al 0.3 Ti 1.7 (PO4)3 is preferred because it is widely used. Furthermore, LATP has a lower reactivity with the electrodes placed in contact with the solid electrolyte than LAGP, which is obtained by replacing titanium (Ti) of LATP with germanium (Ge), and therefore LATP can be used particularly preferably. It is preferable that this mixing and dispersion is accompanied by stirring with a stirrer or application of ultrasonic waves, and the temperature is preferably room temperature because of ease of handling and low cost.

[0018] Through many years of research, the inventors have found that Co is an excellent sintering aid for LATP. In other words, they have found that when Co is present at the interface between LATP powders, sufficient sintering can be performed even at low temperatures, the relative density of the sintered material increases, and the electrical conductivity is also improved. In the course of this investigation, it was also discovered that a large amount of sintering aid reduces the performance of LATP as a solid electrolyte, for example reducing its electrical conductivity and relative density. Therefore, we have been working hard to find a way to coat the LATP powder evenly with a small amount of Co. As a result, after much trial and error, we found that it would be best to use a solution in which cobalt is dissolved in a solvent that can form an azeotrope with water, and that it would be even better to use cobalt nitrate, in which the nitrate group volatilizes during sintering and only cobalt remains, and that if cobalt nitrate hydrate, especially Co(NO3)2·6H2O, is used as the cobalt nitrate, an even smaller amount of Co can be uniformly coated on the LATP powder. We believe that this is because this solvent dissolves nitrate hydrate well, has low surface tension, and also has low interfacial tension with LATP, so it blends well with the surface of LATP to form a uniform liquid film, and the solution is removed evenly when the liquid film dries.

[0019] With regard to the amounts of the solid electrolyte base material and the cobalt salt added, it is preferable that the ratio B / A of the molar amount B of the cobalt salt to the molar amount A of the solid electrolyte base material is 0.001 or more and 0.1 or less. By setting the amount added within this range, a sintered body with high relative density and high electrical conductivity can be obtained.

[0020] Thereafter, the dispersion is dried to obtain a solid (step S03). The drying method may include heat drying and vacuum drying.

[0021] Next, the solid aggregates are crushed to obtain a powder, which is then pressure molded (step S04). Here, examples of the crushing method include a method using a pestle and mortar, and a ball mill. For molding, for example, uniaxial pressure molding, CIP (Cold Isostatic Pressing), sheet molding, etc. can be used, and the pressure can be, for example, 20 MPa or more and 350 MPa or less. The atmosphere for pressurization can be air, Ar gas, N2 gas, or O2 gas, but air is preferably used because it is easy to handle and has low costs.

[0022] The structure of the powder 1 thus obtained is shown in FIG. The powder 1 has a structure in which a solid electrolyte base material 11 made of LTP, LATP, LAGP, or the like is covered with a coating material 12 made of a cobalt salt. Here, the coating material is dense with a uniform thickness and few breaks or defects. The thickness of the coating material is preferably controlled on the order of atomic layers. Specifically, it is preferably 1 to 10 atomic layers, more preferably 1 to 4 atomic layers, and even more preferably 1 to 2 atomic layers. This thickness can be controlled by the amount of cobalt salt to be charged, that is, the ratio B / A of the molar amount B of the cobalt salt to the molar amount A of the solid electrolyte base material. In particular, by using a solvent that can be azeotroped with cobalt nitrate and water, uneven distribution of cobalt is less likely to occur, making it possible to form an ultra-thin film controlled on the order of atomic layers with reduced unevenness. When the coating material is such a thin film, dense and sufficient sintering can be achieved while reducing the amount of sintering aid used. This makes it possible to obtain sufficient performance required of a solid electrolyte, such as high relative density and high electrical conductivity, even at a low sintering temperature.

[0023] The cobalt in this powder has not been subjected to high-temperature treatment until the powder is formed, which would cause it to diffuse into the solid electrolyte base material, and so it does not penetrate into the solid electrolyte base material 11, but exists only in the coating material 12. This allows the amount of cobalt to be kept to a minimum necessary to function as a sintering aid that increases the density of the solid electrolyte, making it possible to produce a solid electrolyte with high performance.

[0024] Incidentally, the presence of cobalt means that it is contained as a component, and the absence of cobalt means that it is not contained as a component. Here, cobalt unintentionally mixed in as an impurity is treated as not being contained. It is preferable that cobalt is not contained as an impurity in the solid electrolyte base material 11, but it is preferable to determine whether to increase the purification purity for that purpose in consideration of cost performance.

[0025] Thereafter, sintering is carried out in an environment in which oxygen is present, such as the air (step S05). The sintering temperature is preferably 600° C. to 800° C., and more preferably 800° C. The time for which this upper limit temperature is maintained can be, for example, 1 Hr to 10 Hr, and the rate of temperature increase and decrease can be, for example, 100° C. / Hr to 300° C. / Hr. Under such sintering conditions, diffusion is unlikely to occur between the solid electrolyte and the electrodes arranged in contact with it, and secondary batteries produced using this solid electrolyte have high performance. Oxygen oxidizes cobalt and it becomes a highly efficient sintering aid, so that a solid electrolyte with high relative density and high electrical conductivity required for secondary batteries can be supplied even at a low sintering temperature of 800°C. Sintering in air is preferable because it is easy to handle and has cost benefits.

[0026] The sintered body 101 thus formed is a solid electrolyte consisting of a sintered body with a bulk portion 21 made of NASICON-type LTP and cobalt oxide present in the neck portion 22, as shown in Fig. 1. The neck portion 22 contains cobalt oxide other than NASICON-type LTP, but in a small amount, so the deterioration of electrical properties due to the presence of cobalt oxide is slight. On the other hand, the bulk portions 21 are sufficiently adhered to each other in the neck portion 22, resulting in a sintered body 101 with a high relative density.

[0027] It should be noted that the present invention is not limited to the above-described embodiments, which are merely examples for explaining the present invention. Anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included within the technical scope of the present invention. In addition, the above explanation has been given with a solid electrolyte for an all-solid-state secondary battery in mind, but the application of this solid electrolyte is not limited to all-solid-state secondary batteries, and it can also be applied to, for example, separators, CO sensors, capacitors, electrochemical devices, and the recovery of lithium ions from seawater. EXAMPLES

[0028] The present invention will be described in more detail below using examples, but the present invention is not necessarily limited to the following examples.

[0029] Example 1 First, cobalt nitrate hexahydrate (Wako) was prepared to prepare the nitrate that would become the sintering aid, and it was dissolved in a solvent consisting of commercially available ethanol that had not been subjected to any dehydration treatment to prepare a nitrate solution (Step S01 in Figure 2). Here, this dissolution was carried out at room temperature in the air. Next, commercially available LATP powder (TOSHIMA Manufacturing Co., Ltd.) with a NASICON-type structure was prepared as the solid electrolyte base material, and it was dispersed in a nitrate solution under ultrasonic application and stirred to produce a dispersion liquid (slurry) (step S02). The environment was atmospheric pressure and room temperature. Here, the amount of LATP was set to an amount that would result in a solid concentration of 15 vol% in the ethanol solvent, and the amount of cobalt nitrate hexahydrate was weighed using an electronic balance so that the weight ratio of Co to the weight of LATP was 0.1 to 2.0 wt% (the molar ratio of Co to LATP was 0.006506 to 0.130123).

[0030] The obtained slurry was then spread evenly and flatly in a disposable container and dried for 1 hour at atmospheric pressure in an oven at 50°C (step S03). The dried sample was ground in an agate mortar without applying force to break down coarse solids produced by the drying process. Thereafter, the resulting crushed product, LATP to which Co had been added (Co-LATP), was filled into a metal mold and pressed to obtain a molded body (step S04). The pressure at that time was set to 100 MPa, and pressure was applied under atmospheric pressure for 3 minutes. Finally, the obtained molded body was sintered at atmospheric pressure at various temperatures (800°C, 1000°C) to obtain a sintered body (step S05). At this time, the temperature increase rate was 100°C / Hr, the maximum temperature was maintained for 10Hr, and the temperature decrease rate was 100°C / Hr.

[0031] The sintering temperature dependence of the relative density of Co-LATP is shown in Figure 4, where the parameter is the amount of Co added and the sintering temperature is set to two levels, 800°C and 1000°C. Here, the relative density was measured as bulk density (volume / weight). The figure also shows the relative density before sintering (this data is displayed at 25°C). At a sintering temperature of 800°C, all LATP sintered bodies with added Co had a higher relative density than LATP without added Co, indicating that the addition of Co contributes to improving the relative density.

[0032] Figure 5 shows the relative density and the Co-addition dependence of the sintered body (Co-LATP) produced by the above process in air at a sintering temperature of 800°C. By adding 0.1wt% Co (molar ratio to LATP is 0.006506), the relative density increases by about 20% from about 59% without Co to about 71%, and by adding 0.2wt% to 2.0wt% Co (molar ratio to LATP is 0.013012 to 0.130123), the relative density exceeds 75%, and when 0.3wt% Co (molar ratio to LATP is 0.019518) is added, the relative density reaches a maximum of about 80%. When 10wt% Co (molar ratio to LATP is 0.650617) is added, the relative density is 54.54% and the sintering shrinkage is -10.23%. When no Co was added, the relative density was 58.63% and the sintering shrinkage was -6.84%, and the addition of a large amount of Co, such as 10 wt%, did not produce a significant effect on improving the relative density.

[0033] Figure 6 shows the dependence of relative density on the amount of Co added for samples fabricated under the same conditions as in Figure 5, except that the sintering atmosphere was changed from air to Ar gas. Under sintering conditions without oxygen, the improvement in relative density due to the addition of Co is only slight, unlike sintering in which oxygen is present. This shows that the oxidation of Co contributes greatly to the mechanism of the improvement in relative density. This result shows that the presence of oxygen is preferable as a sintering environment.

[0034] Figure 7 is an SEM photograph of the fracture surface structure of LATP without Co added, sintered at 800°C in air, and Figure 8 is an SEM photograph of the fracture surface structure of Co-LATP sintered under the same conditions except for the addition of Co. Figures 7(a) and (b) are at different magnifications, with (a) being 10 times that of (b), and Figures 7(a) and 8 being at the same magnification. From these results, it was found that the grain growth of Co-added LATP was not promoted as much as that of Co-unadded LATP, and the addition of Co caused the formation of necks between each grain.

[0035] Figure 9 is an SEM photograph of the fracture surface structure of Co-LATP sintered at 1000°C in air. Sintering has progressed more than that of Co-LATP sintered at 800°C shown in Figure 8, and a densified structure was observed.

[0036] Figure 10 shows the results of measuring the electrical conductivity of Co-LATP sintered at 800°C in air. The electrical conductivity increased with increasing Co content up to 0.5 wt% (molar ratio to LATP: 0.032531). The electrical conductivity decreased from 1.0 wt% Co content (molar ratio to LATP: 0.065062) onwards, but was equal to or higher than the electrical conductivity without Co. It is believed that up to 0.5wt% Co added, the increase in density is the main factor that contributes to the improvement of electrical conductivity. When the Co added amount is 1.0wt% or more, the influence of the impurity phase becomes significant, and this is thought to be why the electrical conductivity starts to decrease.

[0037] Figure 11 shows the results of measuring the electrical conductivity of Co-LATP sintered at 1000°C in air. The electrical conductivity decreased with increasing Co addition. At 1000°C, LATP without Co addition was fully sintered, and it is considered that the difference in the amount of impurity phase generated by the addition of Co is reflected in the electrical conductivity in all samples due to the difference in density. [Industrial Applicability]

[0038] The present invention provides a NASICON-type LTP solid electrolyte having high density and excellent electrical conductivity, an easily sinterable powder suitable for its production, and a method for producing an easily sinterable NASICON-type LTP solid electrolyte having high density and excellent electrical conductivity, which is sintered at 800° C. or less, at which diffusion of the positive electrode active material is sufficiently suppressed. By using this solid electrolyte, the powder for producing the solid electrolyte, and the method for producing the solid electrolyte, lithium ion all-solid-state secondary batteries having excellent mechanical and electrical properties can be supplied with good productivity and at low cost, which is believed to contribute to industry, regardless of whether it is for consumer or industrial use. [Explanation of symbols]

[0039] 1: Powder 11: Solid electrolyte base material (LATP) 12: Cobalt-containing coating material 21: Bulk section 22: Neck 101: Sintered body

Claims

1. The bulk part is made of NASICON type LTP, The neck portion is a solid electrolyte made of a sintered body containing cobalt oxide. A solid electrolyte, wherein the weight percent concentration of cobalt (Co) relative to the NASICON-type LTP is 0.1 wt % or more and 0.5 wt % or less.

2. 2. The solid electrolyte according to claim 1, wherein the bulk portion comprises one or more electrolytes selected from the group consisting of NASICON-type LATP and NASICON-type LAGP.

3. The solid electrolyte according to claim 1, wherein the bulk portion comprises NASICON type LATP.

4. A powder comprising a solid electrolyte base material and a coating material covering a surface of the solid electrolyte base material, The solid electrolyte base material is made of NASICON type LTP, the coating material includes cobalt (Co) ions; The powder for producing a solid electrolyte, wherein the coating material has a thickness on the order of an atomic layer.

5. The powder according to claim 4 , wherein the solid electrolyte base material is one or more selected from the group consisting of NASICON-type LATP and NASICON-type LAGP.

6. The powder of claim 5 , wherein the solid electrolyte matrix comprises NASICON type LATP.

7. 7. The powder according to claim 4, wherein cobalt ions are contained only in the coating material.

8. The powder of claim 4 , wherein the coating material comprises cobalt nitrate.

9. dissolving a cobalt salt in a solvent capable of forming an azeotrope with water to form a solution; A solid electrolyte base material made of NASICON type LTP is put into the solution and dispersed to prepare a dispersion (slurry); drying the dispersion to obtain a solid; pulverizing the solid material to obtain a powder containing cobalt ions; Molding the powder to obtain a molded body; The molded body is sintered in an environment in which oxygen is present.

10. The method for producing a solid electrolyte according to claim 9, wherein the solid electrolyte base material is one or more selected from the group consisting of NASICON-type LATP and NASICON-type LAGP.

11. The method for producing a solid electrolyte according to claim 9, wherein the solid electrolyte base material is a NASICON type LATP.

12. 12. The method for producing a solid electrolyte according to claim 9, wherein the cobalt salt is cobalt nitrate.

13. The cobalt nitrate is Co(NO 3 ) 2 ・6H 2 The method for producing a solid electrolyte according to claim 12, wherein

14. 14. The method for producing a solid electrolyte according to claim 9, wherein the solvent comprises at least one selected from the group consisting of methanol, ethanol, and propanol.

15. The method for producing a solid electrolyte according to claim 14, wherein the solvent is ethanol.

16. The method for producing a solid electrolyte according to claim 9 , wherein the sintering is performed in an air environment.

17. 17. The method for producing a solid electrolyte according to claim 9, wherein the sintering temperature is 600°C or higher and 800°C or lower.

18. 18. The method for producing a solid electrolyte according to claim 9, wherein a ratio B / A of a molar amount B of the cobalt salt to a molar amount A of the solid electrolyte base material is 0.001 or more and 0.1 or less.

Citation Information

Patent Citations

  • Solid electrolyte, preparation method thereof, all-solid-state lithium ion battery and manufacturing method of all-solid-state lithium ion battery

    CN112768758A

  • All-solid type secondary battery, and method for manufacturing the same

    JP2015011864A

Cited By

  • Method for densifying LATP electrolyte sheet through cold sintering-hot pressing coupling

    CN122051355A